(untitled) (Sociologisk Forskning, 2018)
From chatter to organized networks. How think tanks work to enrol others Think tanks, both inside and outside the Swedish context, appear as something of a conundrum. Definitions and conceptual understandings of what think tanks actually do have not been adequately developed. One of the most urgent and unanswered questions regards how we understand the ability of think tanks to get other actors in the political landscape to use their ideas? Drawing on insights from 13 think thanks in Stockholm, the intention of this paper is to provide an empirically based and theoretically informed answer to this question. The results show that the activities colloquially termed ”networking” and ”agenda setting”, can be understood from an organisational perspective. These activities come across as intangible with uncertain outcomes but cannot be seen as random attempts to bridge think tankers and policy actors, but as decided actions designed to make other actors use their ideas in the future. At the same time, the organized relationships to other actors are ambiguous, as too close relationships may risk the think tank’s appearance of independency.